5mw hybrid power generation with agriculture and forestry biomass waste co-ıncineration in stoker and subsequent solar panel (csp) orc station - Tosun, Yıldırım İsmail (IJRER, 2015)
As you know, our country has the world's leading bio- energy resources and a very advantageous position in terms of biomass energy; just as the earth's biomass region corresponding to the portion located between 7% and 12% in Europe in terms of biomass potential with this location first, and is ranked seventh in the world. When the use of biomass resources in our country, about 76% close of the heating application to the appropriate areas, according to other uses of the area around 13%, and the part about 7% appear to be economically viable to produce electricity. May 21, 2009 adopted the "Electricity Energy Market and Supply Security Strategy Document" in, has attributed particular importance to renewable energy sources and the use of the entire hydroelectric potential by 2023, wind power installed capacity of 20.000MW to, the installed 640 MW electricity of geothermal resources, 130MW of generating capacity from biomass sources. There are various objectives to make the necessary arrangements to increase the use of biomass and solar energy as the other device. Considering the known biomass area of the potential high forest fields in northern Anatolia and located in central and eastern Anatolia it is seen as having low to medium heat resources. As we have seen in our country there is a significant potential for biomass resources will be invested. The 5MW hybrid ORC electricity production for low heat sources with CSP will be great source for waste heat and co electricity production on 60-70 % thermal performances by co generation.
Keywords: ORC; Biomass; Solar Panel Station; Co-electricity Production; CSP; biomass